The detection of drugs of abuse and pharmaceuticals in drinking water using solid-phase extraction and liquid chromatography-mass spectrometry. (May 2019) - Peng, Yan; Gautam, Lata; Hall, Sarah W.
Abstract: Pharmaceuticals and drugs of abuse including novel psychoactive substances (NPS) are emerging as newer contaminants in the aquatic environment. The presence of such pollutants has implications on the environment as well as public health and therefore their identification is important when monitoring water quality. This research presents a new method for the simultaneous detection of 20 drugs of abuse and pharmaceuticals in drinking water, including 15 NPS, three traditional illicit drugs and two antidepressants. The developed method is based on the use of solid-phase extraction (SPE) followed by liquid chromatography-mass spectrometry (LC-MS). The SPE recoveries for the majority of target analytes ranged between 62 and 107%. The method detection and quantification limits ranged between 0.01 and 1.09 ng/L and 0.02–3.64 ng/L respectively. Both instrumental and method precisions resulted in relative standard deviations <15.04%, with an accuracy of < ±8.66%. The results show that LC-MS can be an alternative to the more popular technique of liquid chromatography-tandem mass spectrometry for the analysis of drugs of abuse and pharmaceuticals in drinking water. This newly developed simultaneous detection method has been applied to drinking water collected from the East Anglia region of the UK. Citalopram, cocaine, fluoxetine, ketamine, mephedrone, methamphetamine and methylone were detected at the range of 0.14 and 2.81 ng/L. This is the first time that the two NPS mephedrone and methylone, have been detected in UK drinking water. Highlights: A simultaneous and sensitive LC-MS method for detecting drugs in drinking water. Detection method for 20 drugs of abuse and pharmaceuticals including 15 NPSs. 5 drugs of abuse and 2 antidepressants detected in samples from East Anglia, UK. Mephedrone and methylone have been detected in drinking water for the first time.